Sacred Sustenance: A Maudhu’i Inquiry into the Integrated Quranic Paradigm of Consumption - Muhammad Fathur Rozaq (Yayasan Pesantren Mahasiswa An-Nur, 2026)
This study explores the pedagogical architecture of food in the Qur’an through a thematic exegesis (tafsir maudhu‘i) of 55 selected verses. It argues that the Quranic discourse on food transcends simple dietary regulations, forming a systematic ‘alimentary circuit’ designed for moral and spiritual integrity. The research identifies four interconnected dimensions: the Ontological (food as a divine sign), the Normative (legal boundaries of halal-haram), the Axiological (ethics of restraint and social justice), and the Eschatological (consumption as a bridge to the afterlife). Central to this paradigm is the synthesis of Meccan and Medinan revelations. The Meccan phase establishes a theological buffer by anchoring consumption in Rububiyah (Divine Sovereignty), while the Medinan phase provides the legal framework. This study finds that modern consumption often suffers from a